Volumetric two-photon fluorescence imaging of live neurons using a multimode optical fiber - Turcotte, R; Schmidt, CC; Booth, MJ; Emptage, NJ (Optical Society of America, 2020)
Multimode optical fibers (MMFs), combined with wavefront control methods, have achieved minimally invasive in vivo imaging of neurons in deep-brain regions with diffraction-limited spatial resolution. Here, we report a method for volumetric two-photon fluorescence imaging with a MMF-based system requiring a single transmission matrix measurement. Central to this method is the use of a laser source able to generate both continuous wave light and femtosecond pulses. The chromatic dispersion of pulses generated an axially elongated excitation focus, which we used to demonstrate volumetric imaging of neurons and their dendrites in live rat brain slices through a 60 µm core MMF.